Long-term audit of the use of fresh frozen plasma in a university hospital. Issue 5 (October 2017) - Abdel Gader, Abdel Galil M.; Al-Ghumlas, Abeer K.; Al Momen, Abdul Kareem M.; Awadalla, Sitel Banat A.; Badri, Motasim
الملخص: أهداف البحث: هناك قلق عالمي بشأن الاستخدام غير الملائم للبلازما المجمدة الطازجة. أجريت هذه الدراسة للكشف عن مدى الاستخدام غير الملائم للبلازما المجمدة الطازجة في مستشفى الملك خالد الجامعي، بالرياض، وللتأكد من ما إذا كانت هناك أي خطوط توجيهية يتم اتباعها أثناء الاستخدام السريري لها. طرق البحث: قامت هذه الدراسة بتحليل الاستهلاك السنوي من البلازما المجمدة الطازجة في مستشفى الملك خالد الجامعي خلال الفترة من ١٩٨٦ إلى ٢٠٠٧. بعد ذلك، تم استخراج نتائج اختبارات فحص التخثر من السجلات الطبية لـ ٥٣١ مريضا متتاليا من عدة تخصصات في المستشفى لمزيد من التحليل. النتائج: تم صرف ما مجموعه ٦٨٤٨٠ وحدة من وحدات البلازما المجمدة الطازجة خلال الـ٢٢ عاما من الدراسة. وارتفع الاستهلاك إلى هضبة، إلا أنه انخفض بشكل كبير بنسبة ٣٠.٩٪، في عام ١٩٩٥ إلى أدنى مستوى له في عام ٢٠٠٠. وكان هناك أيضا انخفاض متزامن ومتداخل في استهلاك كل من البلازما المجمدة الطازجة ومجموع وفيات المستشفى لكل حالة دخول. وصُرف ما مجموعه ١٦٢٠ وحدة من البلازما المجمدة الطازجة لـ ٥٣١ مريضا، وأجري اختبار التخثر قبل وبعد إعطائه في جميع المرضى تقريبا لقسم التوليد وأمراض النساء و٩٠٪ من المرضى في قسم الجراحة. الاستنتاجات: تم الكشف عن الدرجة الكبيرة من الاستخدام غير الملائم للبلازما المجمدة الطازجة في مؤسستنا عن طريق الانخفاض الملحوظ في الاستهلاك بعد "خوف فيروس نقص المناعة البشرية" العالمي في أوائل التسعينات من القرن الماضي. ويعكس الانخفاض الناتج في إجمالي الوفيات في المستشفى المصاحب للانخفاض المتزامن في استهلاك البلازما المجمدة الطازجة فوائد الاستفادة من بدائل علاج الدم. تم تطبيق اختبار التخثر إلى حد مُرضٍ. يمكن لعمليات التدقيق في سياسات نقل الدم وبرامج التعليم أن تؤدي إلى استخدام أفضل للبلازما المجمدة الطازجة. Abstract: Objectives: There is universal concern about the inappropriate use of fresh frozen plasma (FFP). This study aimed to determine the extent of the inappropriate use of FFP at a university hospital in KSA. Methods: Medical records on the annual use of FFP were analysed from 1986 to 2007. Then, the results of the coagulation screening tests were extracted from the medical records of 531 consecutive patients in various departments of the hospital. Results: As many as 68, 480 FFP units were used during the 22 year study period. Consumption increased and then plateaued in 1995, but dropped dramatically by 30.9% and reached its lowest level in 2000. There was also a concomitant and overlapping drop in both FFP usage and the hospital mortality rate per patient admission. One-thousand-six-hundred-twenty FFP units were issued for 531 patients. Coagulation testing, before and after infusion, was adopted in almost all patients in the Department of Obstetrics and Gynaecology, in 90% of patients in the Department of Surgery and in approximately 70% of patients in other departments. Conclusions: Significant inappropriate use of FFP at our institute has been made evident by examining the remarkable drop in use following the universal "HIV scare" of the early 1990s. The resulting drop in the hospital mortality rate, accompanying the simultaneous drop in FFP use, reflects the benefits of resorting to the use of less blood therapy. Coagulation testing was used to a satisfactory extent. Transfusion audits and educational programs could result a better use of FFP.